A construção resultativa e sua representação por bilíngues do par linguístico português do Brasil e inglês - Candido Samuel Fonseca de Oliveira (2013)
Based on theoretical perspectives such as multicompetence, superset-subset relation between languages, and construction grammar, the present study sought to investigate the issue of activation of linguistic representation in L2 users minds. For that purpose, it has been examined a grammatical phenomenon, which reflects mapping of semantic configuration onto syntactic structure, more specifically, issues related to the realization of argument structure. Utilizing an experiment with the magnitude estimation paradigm, it was analyzed how the resultative construction is represented by bilinguals of Brazilian Portuguese and English. This study suggests that the languages present in the linguistic system of an L2 user are somehow connected in the syntactic level. Two phenomena corroborate this idea: L1-L2 and L2-L1 influence. This study is also in accordance with the conjectures originated from the construction grammar, since it suggests that linguistic representations, even those from the dominant language, come from and are modified by the use of a second language. Furthermore, the present study addresses the L2 users accuracy in the acquisition of the resultative construction. As predicted by the ideas originated from superset-subset relation between languages, the result indicates that bilinguals learn this construction; however, they are not as sensitive as monolinguals to perceive the restrictions present in it. Consequently, the overgeneralization of L2 rules seems to be part of the acquisition of the resultative construction. Moreover, this study has empirical data concerning the grammar of the resultative construction. Therefore, while the experiment focused primarily on aspects related to bilingual representation, it was also able to shed light on issues paramount to the linguistic description of both Brazilian Portuguese and English.